A participatory planning model in the context of Historic Urban Landscape: The case of Kyrenia's Historic Port Area. (March 2021) - Kırmızı, Özge; Karaman, Aykut
Highlights: Kyrenia Historic Port Area was studied with respect to the aspects elaborated in the Historic Urban Landscape approach. A relatively more inclusive and participatory model was proposed, which can be incorporated in Management Plans. Ballarat Site Management Plan as conceptual framework was examined and the methods and management mechanisms were analyzed. The involvement of academic and scientific institutions was found to be key in the conservation process. The community and stakeholder participation in Kyrenia Port Area was found to be necessary to reflect all the values of the historical and cultural heritage. Abstract: Urban areas are constantly changing due to the pressures of migration and rapid growth in urban populations. As a result, historically and culturally significant sites are under increased risk of deterioration and this affects the urban sustainability transitions culturally and socially. Thus, an operationally multidimensional conservation management framework is needed with new approaches to historic heritage sites, in which urban dynamics are considered extensively. Historic Urban Landscape (HUL) concept, which was launched by UNESCO in 2011 brought a new comprehensive perspective with parameters to help protect heritage areas in more sustainable ways. The parameters of HUL consists of aspects such as but not limited to landscape, culture, stakeholders, diversity, sustainability, multidisciplinary cooperation, equity, participation, and building capacity. This new approach was developed for relatively more sustainable and integrated ways to protect heritage in the urban context. It is also a management tool to support the Site Management Plans more holistically in the conservation of historic and cultural heritage sites within the World Heritage List. In this research, Kyrenia Historic Port Area was studied with respect to the aspects elaborated in the Historic Urban Landscape approach of UNESCO. A sustainable and participatory conservation process was found to be lacking due to the institutional, economic and political challenges. In that context, a relatively more inclusive and participatory model was proposed, which can be incorporated in Management Plans. In order to test the applicability of the concept of the Historic Urban Landscape in the stated area; internationally applied field management plans, Turkish Republic of Northern Cyprus (TRNC) laws, provisions, and ordinances have been examined through the review of the relevant literature. Additionally in the context of heritage site protection, the purpose, definition, processes, and components of the Site Management Plans were discussed. In regard to the proposed model, The Australian Ballarat Site Management Plan as conceptual framework was examined and subsequently the methods and management mechanisms were analyzed. In result of the analyses, a proposed innovative model was discussed in order to determine the flow of the management system of Kyrenia in the historic port area and to ensure the participation of stakeholders in the decision-making as well as the conservation of the area, which are essential elements in establishing more sustainable conservation and management of heritage sites not only in the city of Kyrenia but also in other parts of the country and the Island as a whole.